2014
DOI: 10.1371/journal.pcbi.1003887
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Signatures of Reorganised Brain Networks in Disorders of Consciousness

Abstract: Theoretical advances in the science of consciousness have proposed that it is concomitant with balanced cortical integration and differentiation, enabled by efficient networks of information transfer across multiple scales. Here, we apply graph theory to compare key signatures of such networks in high-density electroencephalographic data from 32 patients with chronic disorders of consciousness, against normative data from healthy controls. Based on connectivity within canonical frequency bands, we found that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
168
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 207 publications
(190 citation statements)
references
References 61 publications
17
168
4
1
Order By: Relevance
“…This pattern was further enhanced in emerged from MCS patients, and was strikingly evident in patients with locked-in syndrome and controls. We have previously demonstrated that such frontoparietal patterns of alpha connectivity are neural markers of behaviourally evidenced consciousness, not only in patients with disorders of consciousness (Chennu et al, 2014), but also during propofol sedation (Chennu et al, 2016). The connectivity patterns in Fig.…”
Section: Eeg Metrics and Behavioural Awarenessmentioning
confidence: 87%
See 4 more Smart Citations
“…This pattern was further enhanced in emerged from MCS patients, and was strikingly evident in patients with locked-in syndrome and controls. We have previously demonstrated that such frontoparietal patterns of alpha connectivity are neural markers of behaviourally evidenced consciousness, not only in patients with disorders of consciousness (Chennu et al, 2014), but also during propofol sedation (Chennu et al, 2016). The connectivity patterns in Fig.…”
Section: Eeg Metrics and Behavioural Awarenessmentioning
confidence: 87%
“…Alongside, the cross-spectrum between the spectral decompositions of every pair of channels was used to calculate the debiased weighted phase lag index (dwPLI) measure (see Supplementary material for further details) introduced by Vinck et al (2011). We used this tried-and-tested measure (Chennu et al, 2014(Chennu et al, , 2016Kim et al, 2016) to estimate brain connectivity between pairs of EEG channels in our dataset. Further, we restricted analysis to the delta, alpha and theta bands, as the impact of the considerable electromyographic artefact observed in patients was relatively negligible in these bands.…”
Section: Eeg Data Analysismentioning
confidence: 99%
See 3 more Smart Citations